Синергетичний підхід в структурі методології історико-правових досліджень - Кудін, С.; Kudin, S. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У даній статті її автором доведено, що особливості використання синергетичного підходу зумовлені обмеженням «історичної площини» дослідження та необхідністю з’ясування впливу флуктуацій-відхилень на той чи інший сценарій «розвитку подій». Виявлено можливості синергетичного підходу при проведенні досліджень у сфері альтернативної історії права. З’ясовано, що застосування синергетичного підходу в історико-правових дослідженнях має ряд специфічних проблем: виявлення сутності обміну між «історично-правовою системою» та «навколишнім середовищем» речовиною, інформацією, енергією; обмеження використання математичних методів; пошук критеріїв розмежування об’єктивних і суб’єктивних факторів, які вплинули на вибір саме даного «сценарію подій» у точці біфуркації; розмежування самоорганізації структурних елементів системи та їх організації як наслідку управлінсько-владного втручання та ін. The article highlights the importance of the synergetic approach for the study of the historical events development. The author has proved that the specificity of synergetic approach application is caused by the restrictions of the «historical research plane» and the necessity to clarify the impact of fluctuationvariations on this or that particular scenario of the «course of events» development. The author reveals the possibilities of synergetic approach in research ofthe issues of the alternative history of law, which can be applied in the modeling of situations with the viewof the past and taking into account the impact of the future on the present day events. It has been foundout that the application of synergetic approach inthe field of the historical and legal research has a number of specific problems, such as: revealing the matter of exchange between the «historical and legal system» and «environment» (substance, information, energy); restrictions for the use of mathematical methods; searching criteria for delineation of objective and subjective factors that influenced the choice of this or that particular «scenario of events» at the bifurcation point.
Synergetic Approach as a Structural Component of Historical and Legal Research Methodology
Keywords: синергетичний підхід; методологія; історія права; історико-правові дослідження; історично-правова система; synergetic approach; methodology; history of law; historical and legal research; historical and legal system